Chamelia and the New Kid in Class - Long, Ethan (USA, 2013)
Chamelia is used to being the star of her class, so when Cooper, a new student, becomes the center of attention, she is determined not to like him...
Keywords: Animals; Friendship; Juvenile Fiction; Reptiles & Amphibians